Sosialisasi Pembuatan Obat Anti Nyamuk Alami Untuk Penguatan UMKM di Desa Mekar Mulio - Rambe, Ahmad Sampurna; Dimas, Dimas; Sabila, Umaira; El Rahmah, Mutiara; Umami, Liza; Defnusza, Qiefana (Civiliza Publishing, 2024)
Mekar Mulio Village, located in Sei Balai District, Batu Bara Regency, North Sumatra, has a lot of agricultural potential, one of which is the lemongrass plant which can be used to make natural mosquito repellent products. However, there are problems related to people's understanding of the existing economic potential and a lack of interest and skills in product diversification. To solve this problem, the KKN 86 group conducted outreach on making natural mosquito repellent using lemongrass. The aim of this outreach is to increase the knowledge and skills of the community, especially PKK women, on how to use lemongrass as an innovative and environmentally friendly product. Socialization about making anti-mosquito medicine from lemongrass was carried out through lectures, discussions and direct demonstrations. The result is that participants are more adept at making natural mosquito repellent and better understand the various types of lemongrass products. The result is an effective mosquito repellent that smells refreshing. The response given by the community, village officials and PKK women showed positive results. The economic potential of lemongrass became clearer to the community, and they were inspired to develop businesses based on natural products. These activities not only offer a practical solution to the mosquito problem, but also strengthen local small and medium businesses and improve community welfare.